Anatomy of strength & conditioning - Liebman, Hollis Lance (Firefly Books, 2014)
Anatomy of Strength and Conditioning is a guide to understanding how to use exercise to increase your muscle power and improve your physique. The 67 exercises and stretches will help increase your stamina for sporting pursuits but also contribute to your function better in daily life. Additionally, there are six specially created workouts that allow you to incorporate varying degrees of intensity into your fitness regime. Regardless of your level of competence, Anatomy of Strength and Conditioning provides clear, step-by-step illustrated instructions, each with useful tips on how to perform the exercise correctly (and what to avoid). Alongside each exercise are detailed anatomical illustrations highlighting the muscles that benefit most. Anatomy of Strength and Conditioning provides everything you need to increase your power and tone in your body.